Utterance in Hadith AL- Hawth as a Rhetorical Study - Mahmoud, Muthanna (Humanities Journal of University of Zakho, 2017)
We usually do not give much importance to the subjects that have relations with rhetorical utterance since it is regarded as a normal literary topic. But talking or dealing with the Holy Quran or AL- Hadith is totally different. The two aforementioned components need high concentration and a precise focus. While analyzing, deviations and stumbles may occur due to the variety of analysis and contemplations for a certain text. Hence, inaccuracy may occur at any time throughout the analysis process. We had to respect three main points in this humble research. First, the researcher found it necessary to sanctify the speech of the Prophet Mohammed (peace and blessings of Allah be upon him). Second, the high status of the Hadith has been taken into account and separated from the other literary texts. Third, the prophetic text has a legislative discourse. Moreover, the brilliant writing of the texts has a sheered positive contribution in guiding the nation and reforming them at the same time. The research is an attempt to uncover some rhetorical aspects from AL- Hadith, its purposes and conditions of uttering it. Finally, the research is not ideal and many researchers have tried it before.